Best suited timing schedule of inorganic NPK fertilizers and its effect on qualitative and quantitative attributes of spring sown sugarcane (Saccharum officinarum L.) - Sajid Hussain; M. Anwar-ul-Haq; Shahbaz Hussain; Zeeshan Akram; Muhammad Afzal; Imran Shabbir (Journal of the Saudi Society of Agricultural Sciences, 2017)
Recently approved variety of sugarcane CPF-248 was grown at agriculture farms of Fatima Sugar Mills, Muzaffargarh, Pakistan. The experiment site was located at Latitude 30°17′52.58″N and Longitude 70°57′44.31″E. This experiment was conducted to sort out a suitable fertilizer timing schedule being practiced in the area. This promising variety was evaluated for inorganic N, P and K at different growth stages throughout the year. Each fertilizer treatment had 60 m long 3 rows at random. Center to center distance of each row was 1.35 m which makes total plot size of 1215 m2. Three budded cane sets were prepared and dipped in 0.25% solution of Thiophinate methyl. After hot water treating at 52 °C for 30 min cane sets were sown in 8 in. deep furrows and buried with almost 1 in. thin layer of soil. There were 5 treatments and each treatment had 3 replications, the experiment was laid out in Randomized Complete Block Design (RCBD). Qualitative and quantitative parameters i.e. germination% age, no. of tillers, stem elongation rate, stem girth, sucrose contents and yield were recorded and periodic trend of these traits were plotted. Significant (P ⩽ 0.05) differences of fertilizer treatments on yield and yield contributing factors were validated. Studied variety responded significantly not only from miller’s and breeder’s point of view but also from sugarcane grower’s point of view. T2 was comparatively least significant while T4 was 2nd and T5 was 3rd most suitable treatments when comparative analysis was done with T1 (control). By evaluating all the studied parameters and value cost ratio (VCR) treatment T3 was most suitable timing schedule of NPK fertilizers.